2018
DOI: 10.1159/000488808
|View full text |Cite
|
Sign up to set email alerts
|

Aflibercept Treatment in Polypoidal Choroidal Vasculopathy: Results of a Prospective Study in a Caucasian Population

Abstract: Introduction: Polypoidal choroidal vasculopathy (PCV) is a choroidal pathology characterized by frequent occurrences of subretinal hemorrhages and resistance to monotherapies such as ranibizumab or bevacizumab intravitreal injections (IVT). The purpose of this study is to evaluate both the anatomical and functional efficacy of aflibercept IVT as a monotherapy in PCV in a Caucasian population. Methods: We conducted a prospective multicenter study in either treatment-naïve patients with PCV or PVC patients who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
2
1
2
Order By: Relevance
“…In line with the literature, we reported a predominance of women, but with a higher mean age (73.9 ± 9.1 years). 1 This particularity of the Caucasian population has also been stressed by Wolff et al 6 and Agorogiannis et al 7 In our population, half of the patients showed associated signs of AMD. Therefore, this suggests a high proportion of type 1 PCV compatible with the Caucasian origin of our cohort.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with the literature, we reported a predominance of women, but with a higher mean age (73.9 ± 9.1 years). 1 This particularity of the Caucasian population has also been stressed by Wolff et al 6 and Agorogiannis et al 7 In our population, half of the patients showed associated signs of AMD. Therefore, this suggests a high proportion of type 1 PCV compatible with the Caucasian origin of our cohort.…”
Section: Discussionsupporting
confidence: 81%
“…5 At 2 years, the PLANET study did not find any difference in VA between the combined treatment (aflibercept-PDT) and aflibercept monotherapy. 4 In our study, VA appeared to have a worse evolution than that described in the PLANET study and in Wolff et al 6 study. This difference could be explained by several aspects: the characteristics of our Caucasian population (older, more patients with associated AMD), the therapeutic regimen without loading dose, and PRN protocol used in our study, involving a smaller number of IVIs.…”
Section: Discussioncontrasting
confidence: 44%
“…A few reports have been performed in Caucasian with the aim of investigating the therapeutic approach of AT1. In the prospective multicenter study of Wolff et al 28 A total of 34 eyes were treated with a fixed-dosing aflibercept during 6 months. The results were a gain of 13 letters and a rate of polyp regression of 62%.…”
Section: Discussionmentioning
confidence: 99%
“…Одно из таких исследований -работа Wolff et al, направленная на оценку показателей эффективности афлиберцепта у 34 пациентов. К концу 6-го месяца терапии среднее улучшение зрения составило 13 букв по шкале ETDRS, при этом у 62 % пациентов отмечалась полная резорбция полипов [36]. Разумеется, для формулирования чётких выводов о применении афлиберцепта у пациентов с ПХВ в европеоидной популяции требуется более обширная доказательная база, однако подобные небольшие работы могут сформировать предварительное мнение о показателях эффективности препарата и в данной подгруппе пациентов.…”
Section: особенности терапии полипоидной хориоидальной васкулопатииunclassified